THE IMPACT OF FATHERLESS ON CHILDREN'S PSYCHOLOGICAL DEVELOPMENT - Zahra, Syaira Sazilla; Fitriani, Wahidah; Yeni, Putri (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
Fatherlessness, or the absence of a father in a child's life, has a significant impact on the child's psychological development. Fathers play an important role in a child's emotional, social and academic balance. This research aims to investigate the impact of fatherlessness or the absence of a father on children's psychological development. This research uses a qualitative methodology approach. Research results show that father absence, whether due to death, divorce, distant work, or other family problems, can cause disparities in children's psychological development.